THE ROLE OF THE FAMILY IN FORMING THE CHARACTER EDUCATION OF THE STUDENTS AT SMP NEGERI 44 SATAP OKU - Hasana, Nur Ihsani; admin, admin (Teaching English as a Foreign Language Overseas Journal, 2022)
This research was conducted with the aim of finding out role family in formation education character participant educate class VII SMP NEGERI 44 SATAP OKU. This type of research, namely qualitative with design study descriptive, to get results study with how to interview. The subjects in this research are family participant educate class VII and class VII 3 students of SMP NEGERI 44 SATAP OKU. How role family in formation education character participant educate class VII. The research results show that the role family in formation education character participant educate class VII SMP NEGERI 44 SATAP OKU educate through example behavior, implement system education early, do system habituation, and giving time And attention dialogue between parents and child